PERAN PEREMPUAN DALAM PENGAMBILAN KEPUTUSAN KELUARGA DI ERA MODERN PERSEPKTIF HUKUM KELUARGA ISLAM - Suryantoro, Dwi Dasa (USRAH: Jurnal Hukum Keluarga Islam, 2025)
The role of women in Islamic families is often seen as limited by traditional norms that prioritize male dominance in decision-making. However, as time progresses, the role of women in the family is getting more and more attention, especially in the modern era that demands equality and a fairer distribution of roles. The purpose of this research is to analyze the role of women in family decision-making in the modern era, as well as to see how the perspective of Islamic family law provides space for women to participate more actively in important family decisions. The method of this research is to use a qualitative method with a library or literature study approach (library research). This method was chosen because the focus of the research is to understand the role of women in family decision-making in the modern era from the perspective of Islamic family law. The results of the research show that the principle of deliberation in Islamic families teaches the importance of collective and inclusive decision-making, which is in line with the value of gender equality. Islamic family law encourages consultation in family matters, where every member of the family, whether male or female, should have equal rights to give their opinion as long as it does not conflict with religious values ​​or Sharia. Keywords: Women's Role, Decision Making, Islamic Family,